Simultaneous development of IgA vasculitis and eosinophilic granulomatosis with polyangiitis. (2nd January 2020) - Asano, Yosuke; Matsumoto, Yoshinori; Miyazaki, Tatsuhiko; Ishizu, Akihiro; Morizane, Shin; Hayashi, Keigo; Yamamura, Yuriko; Hiramatsu, Sumie; Miyawaki, Yoshia; Morishita, Michiko; Ohashi, Keiji; Watanabe, Haruki; et al.
Abstract: Immunoglobulin A (IgA) vasculitis (IgAV) is a small vessel vasculitis presenting cutaneous purpura, arthralgias and/or arthritis, acute enteritis and glomerulonephritis caused by deposition of the IgA1 -mediated immune complex. Eosinophilic granulomatosis with polyangiitis (EGPA) is an anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) characterised by eosinophil-rich and granulomatous inflammation in small to medium-sized vessels. Both IgAV and EGPA are classified as autoimmune systemic vasculitis, but the pathogenesis of immune complex-mediated IgAV and that of pauci-immune EGPA are different. Here we report a rare case of simultaneous development of IgAV and EGPA presenting palpable purpura and numbness in a patient with a history of asthma. Histological examination revealed leukocytoclastic vasculitis with deposition of IgA, IgM and C3 in the upper dermis and necrotising vasculitis with eosinophilic infiltration and granulomatous formation in the lower dermis and subcutaneous fat, indicating the existence of IgAV and EGPA. Our case provides evidence of concurrent development of two different types of vasculitis, which may affect disease-associated complications, therapeutic strategy and prognosis.